An Executive Perspective on Workforce Planning - Emmerichs, Robert M. (RAND Corporation, 2004)
Workforce planning is an activity intended to ensure that investment in human capital results in the timely capability to effectively carry out an organization's strategic intent. This report examines how corporate executives can provide guidance from the top of the organization to the business units that actually carry out the organization's activities so that the strategic is successfully realized.